Factors of Anxiety Symptoms Due to Large-Scale Social Restriction Policy During the COVID-19 Pandemic in Indonesia - Susilowati, Indri Hapsari; Alimoeso, Sudibyo; Nugraha, Susiana; Hasiholan, Bonardo Prayogo; Simanjuntak, Magda Sabrina Theofany; Satria, Nur Rachmat (Kesmas, 2025)
The Indonesian Government took some preventive measures to slow the spread of the COVID-19 virus, including social restrictions and encouraging individuals to stay at home and avoid needless gatherings. This study aimed to identify factors related to anxiety symptoms during large-scale social restrictions. This study employed a cross-sectional design using the snowball technique in an online survey. A total of 788 respondents comprised the target population to detect the smallest effect size (Cohen's dz = .2), with the level of power of 0.8 using G*Power 3.1, specifically targeting adults aged over 18 years. Out of 1,194 people who took part in the survey, 847 completed all the answers. The findings revealed that 42% of participants experienced feelings of nervousness, anxiety, or agitation, and 42.5% became easily agitated during the COVID-19 pandemic. Nonetheless, 81.7% of those surveyed reported being able to manage their concerns, and 80.7% had good time management during the COVID-19 pandemic. Descriptive analysis showed that sex, residence, marital status, number of children, occupational status, being infected by COVID-19, health concern, and time management had a relationship with anxiety symptoms.